1998
DOI: 10.1093/bja/80.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Thiopental or etomidate for rapid sequence induction with rocuronium

Abstract: We have assessed the effect of the choice of i.v. induction agent on intubation conditions, 60 s after administration of rocuronium 0.6 mg kg-1. We studied 60 adult patients, allocated randomly to one of two groups. Anaesthesia was induced with alfentanil 10 micrograms kg-1 followed by thiopental 5 mg kg-1 (AT-R group; n = 30) or etomidate 0.3 mg kg-1 (AE-R group; n = 30). Both groups received rocuronium 0.6 mg kg-1. Laryngoscopy was started 60 s later and intubation conditions were evaluated according to a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 7 publications
2
31
1
8
Order By: Relevance
“…Studies about the influence of hypnotics in neuromuscular blockers onset performed with vecuronium have shown a faster onset with etomidate as compared to thiopental and propofol, which could be attributed to the better hemodynamic profile of etomidate 6 . As to rocuronium, similar results were observed with etomidate and thiopental; however, there has been less diaphragmatic reaction in the etomidate group 20 . In our study, cough and diaphragmatic movement after tracheal intubation were observed with both drugs.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Studies about the influence of hypnotics in neuromuscular blockers onset performed with vecuronium have shown a faster onset with etomidate as compared to thiopental and propofol, which could be attributed to the better hemodynamic profile of etomidate 6 . As to rocuronium, similar results were observed with etomidate and thiopental; however, there has been less diaphragmatic reaction in the etomidate group 20 . In our study, cough and diaphragmatic movement after tracheal intubation were observed with both drugs.…”
Section: Discussionsupporting
confidence: 74%
“…A maioria dos autores correlaciona a influência dos agentes hipnóticos na latência do bloqueio neuromuscular com a estabilidade hemodinâmica e, indiretamente, com o grau de perfusão muscular. O agente hipnótico escolhido para a indução anestésica influencia nas condições de intubação traqueal de várias maneiras: por depressão de reflexos larínge-os e faríngeos aos estímulos da intubação traqueal e também por potencializarem os efeitos de alguns bloqueadores neuromusculares [19][20][21] . Dentre os agentes hipnóticos o propofol é amplamente empregado para a indução de anestesias, por deprimir de maneira significativa os reflexos laríngeos e faríngeos, podendo até mesmo prescindir da ação complementar dos BNM não despolarizantes para a intubação traqueal.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…24 The induction agents such as etomidate and ketamine are known to improve intubation conditions by maintaining cardiac output and blood pressure and accelerating the onset time of rocuronium. 11,21,25 Although our study is in accordance with these studies as Group K has had higher heart rates and shorter onset times than those of Group S, we could not demonstrate better intubation quality scores in Group K. We related this situation to the relatively smaller dose of ketamine used in our study.…”
Section: Discussionsupporting
confidence: 66%